Analisis Efek Moderasi Penerimaan Teknologi Komputasi Awan Pada Mahasiswa Jakarta Selatan - Riskinanto, Anggar; Kelana, Bayu (Institut Teknologi dan Bisnis Kalbis, 2019)
The use of the Internet has penetrated all aspects of life. One of them in the academic world, is used as a solution to share knowledge and collaborate. The use of cloud computing is one example that allows the academic community to do so. Based on the initial interview, cloud computing technology is only used as a document storage media. Therefore this study aims to examine the factors that influence the use of this technology. The research conducted is quantitative and uses purposive random sampling technique. The questionnaire was distributed in the form of paper and Google Form to S1 students majoring in information systems in South Jakarta and obtained as many as 297 respondents. Data processing was done using PLS-SEM, the result of which was that most hypotheses were accepted with the greatest influence on attittude constructs to continued use intention. But in the moderation effect test, all hypotheses are rejected. This means that the use of technology in students is influenced by their attitude. However, it makes no difference for men and women. The same is true for experienced or not students.